Measuring strategic control in implicit learning: how and why? - Norman, Elisabeth (Frontiers in Psychology, 2015)
Several methods have been developed for measuring the extent to which implicitly learned knowledge can be applied in a strategic, flexible manner. Examples include generation exclusion tasks in SRT learning (Destrebecqz & Cleeremans, 2001; Goschke, 1998) and 2-grammar classification tasks in AGL (Dienes, Altmann, Kwan, & Goode, 1995; Norman, Price, & Jones, 2011). Strategic control has traditionally been used as a criterion for determining whether acquired knowledge is conscious or unconscious, or which properties of knowledge is consciously available. In this paper I first summarize existing methods that have been developed for measuring strategic control in the SRT and AGL tasks. I then address some methodologial and theoretical questions. Methodological questions concern choice of task, whether the measurement reflects inhibitory control or task switching, and whether or not strategic control should be measured on a trial-by-trial basis. Theoretical questions concern the rationale for including measurement of strategic control, what form of knowledge is strategically controlled, and how strategic control can be combined with subjective awareness measures.